Method for preparing photoelectric substrate material by using transparent wood and magnetron sputtering technology
Through gradient segmented delignin process and magnetron sputtering technology, transparent conductive composite materials are prepared, which solves the problems of insufficient conductivity and optical performance of transparent wood photoelectric substrates, and achieves efficient conductivity and excellent transparency.
Patent Information
- Application Number
- CN202510013736.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art When preparing transparent wood photoelectric substrates, the electron conductivity and insufficient optical performance are poor, resulting in limited application in electrochromic devices.
The gradient segmented delignin process is used and magnetron sputtering technology is combined with the transparent wood sputtering technology to sputter conductive substances on the surface of transparent wood to prepare transparent conductive composite materials.
The conductive properties and transparency of transparent conductive materials are improved, the resin filling and material properties are optimized, and the mechanical strength and optical transmittance of the material are enhanced.
Smart Images

Figure CN119876875A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of optoelectronic materials, and in particular to a method for preparing an optoelectronic device substrate by using transparent wood. Background Art
[0002] As a natural sustainable material, wood plays an important role in the field of materials with its advantages of low price, easy processing, environmental friendliness and sustainability. Especially in the field of wearable devices, the good optical properties of transparent wood give it a huge advantage. It can be used as a good substrate for devices to replace petroleum-based polymers such as polyethylene and polyethylene terephthalate. However, in the field of electrochromic electrodes, although transparent conductive materials in the existing technology have made certain progress, they still face many deficiencies in practical applications.
[0003] The conductivity of existing transparent conductive materials is often insufficient to meet the requirements of efficient conductive substrates. For example, patent document CN109049215A discloses a transparent and conductive flexible wood composite material prepared by a low eutectic solvent impregnation method, and the conductivity of the material obtained by this method is only 2.5 S / m. This low conductivity limits the application of the material in electrochromic devices that require fast response and high-efficiency conversion. In addition, the material is an ionic conductor and cannot be effectively used as a current collector in a photovoltaic device, which is responsible for evenly distributing the current to the entire electrode surface to ensure the consistency and response speed of the color change.
[0004] The current methods for preparing transparent conductive cellulose films mainly rely on coating conductive materials such as silver nanowires, graphene or carbon nanotubes. However, these methods have obvious disadvantages: silver nanowires are easily oxidized to form silver oxide, resulting in loss of conductivity; graphene and carbon nanotubes are poorly bonded to cellulose films, affecting the optical properties of the final product and reducing the long-term stability of the material. These problems greatly limit the potential of electrochromic electrodes in practical applications.
[0005] The ITO film produced by magnetron sputtering technology under low temperature conditions has poor quality, resulting in unsatisfactory conductivity and transmittance. Although this method is low-cost, efficient and suitable for industrial production, the temperature that cellulose film can withstand is relatively low, making it difficult to achieve high-quality ITO film at low temperatures. In addition, patent CN106205876A proposes to use the "ITO / Ag / ITO" three-layer composite structure to improve conductivity and transmittance, but this method has a complicated preparation process and requires precise control of the growth conditions and annealing treatment of each layer, which increases the process difficulty and cost.
[0006] In summary, the existing technology has many shortcomings in conductivity, transmittance, stability and preparation process, which hinders the widespread application and development of transparent wood in the field of electrochromic electrodes. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a method for preparing a photoelectric substrate material using transparent wood and magnetron sputtering technology, so as to solve the problems of poor electronic conductivity and insufficient optical performance when preparing a transparent wood photoelectric substrate in the prior art.
[0008] In the existing delignification technology, single-factor adjustment process is mostly used to increase the reaction speed and reaction rate, without paying attention to the structure and mechanical properties of the cellulose skeleton, and the improvement of transparent wood performance is very limited. Moreover, the single-factor adjustment method often cannot fully optimize the delignification process, and it is difficult to take into account the performance of transparent wood such as reaction strength and material structural integrity at the same time.
[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: In one aspect, the present invention provides a method for preparing a conductive composite material, comprising the following steps: S1, delignification, placing wood chips in sodium chlorite solution to remove lignin; S2, preparation of transparent wood, impregnating the cellulose skeleton from which lignin has been removed with epoxy resin, and curing the resin to obtain transparent wood; S3. Preparation of transparent conductive composite materials: using magnetron sputtering technology to sputter conductive materials on the surface of transparent wood to obtain transparent conductive composite materials.
[0010] Furthermore, the delignification process in step S1 is a gradient staged process, including three stages; the pH value of the solution used in the three-stage delignification process is increased in gradient, and the stirring speed used in the three-stage delignification process is decreased in gradient; Preferably, in the three-stage delignification process, the concentration of sodium chlorite remains unchanged, which is 2.5wt%; Preferably, in the three-stage delignification process, the pH values of the solutions used are 4, 4.6 and 5.5 respectively; Preferably, in the three-stage delignification process, the stirring speeds used are 300 rpm, 200 rpm and 50 rpm respectively; In order to ensure the transparency and conductive properties of transparent conductive materials, transparent wood is required to have good transparency and a smooth surface.
[0011] Wood is a multi-layer skeleton structure formed by cellulose, hemicellulose and lignin through intermolecular forces. Lignin is the main light-absorbing component in wood, and delignification is a key step in preparing transparent wood. The delignification process removes light-absorbing substances in wood. The lower the lignin content, the higher the transparency of transparent wood.
[0012] The cellulose skeleton structure and elastic modulus obtained after delignification also have an important influence on the final material properties. Hemicellulose connects cellulose and lignin to form an intermediate layer. After wood delignification, a cellulose skeleton is obtained, which can maintain the structure of transparent wood. The hemicellulose in the intermediate layer also gradually decreases with the progress of the reaction. The intermediate layer is removed, which avoids the obstruction of the pores by the intermediate layer, helps the resin to evenly fill the pores during the impregnation process, avoids the formation of pores, and improves the transparency of transparent wood. However, if the delignification reaction is too intense in the later stage, it will not only destroy the structure of hemicellulose and cellulose, which may cause the pores to collapse and the resin cannot enter the pores, but also reduce the elastic modulus of the cellulose skeleton, thereby weakening the mechanical strength of the cellulose skeleton.
[0013] After resin impregnation and before curing, the resin is in a flowing state. At this time, the cellulose skeleton must have sufficient elastic modulus to maintain its structural integrity and prevent the cellulose skeleton from collapsing due to filling with resin under weak supporting force. If the cellulose skeleton collapses, it will cause uneven thickness of transparent wood, damaged surface flatness and reduced transparency.
[0014] Thermal curing can significantly accelerate the curing speed of transparent wood. However, since transparent wood is composed of a cellulose template and an impregnated resin, there is a difference in the thermal shrinkage of the two. During the thermal curing process, this different thermal shrinkage behavior will lead to uneven internal stress, which in turn causes the formation of microcracks. Some resins are prone to produce larger interface pores with the cellulose skeleton, affecting the optical transparency and surface smoothness of the material. Although curing at room temperature can solve the above problems, its curing speed is slow; and in the early stage of the curing process, the resin is prone to flow and migration under the action of gravity, especially in the horizontal direction, which may cause uneven resin distribution.
[0015] The extreme smoothness of the transparent wood surface is crucial for the uniform deposition of conductive materials during magnetron sputtering coating. Only when the surface flatness is strictly guaranteed can the uniform coverage of the conductive layer be achieved, thus ensuring that the material has excellent conductive properties. On the contrary, an uneven surface will directly affect the quality of the sputtered layer, thereby weakening the conductive properties and reducing the overall performance.
[0016] Considering the above-mentioned influencing factors, it is necessary to propose a gradient segmented delignification process that can not only completely remove lignin and ensure high transparency, but also maintain the structural integrity of the cellulose skeleton and its appropriate elastic modulus to maintain the mechanical strength and surface smoothness of the wood.
[0017] Specifically, the delignification process in step S1 includes the following steps: S1.1, wood chips were placed in a solution of sodium chlorite with a concentration of 2.5wt% and a pH of 4, and the temperature was maintained at 90°C under magnetic stirring at 300rpm. After reacting for 1h, the wood chips were taken out and washed with deionized water for 3 times; S1.2, place the washed wood chips in a solution with a sodium chlorite concentration of 2.5wt% and a pH of 4.6 (the pH of the solution is adjusted with glacial acetic acid), and keep the temperature at 90°C at a magnetic stirring speed of 200rpm. After reacting for 1 hour, take out the wood chips and wash them with deionized water three times; S1.3, the washed wood chips were placed in a solution with a sodium chlorite concentration of 2.5wt% and a pH of 5.5 (the pH of the solution was adjusted with glacial acetic acid), and the temperature was maintained at 90°C at a magnetic stirring speed of 50rpm. After reacting for 1h, the wood chips were taken out and washed with deionized water for 3 times; Preferably, step S1 further comprises the following steps: S1.4, soaking the wood chips in anhydrous ethanol for preservation; Preferably, in the step S2 of preparing the transparent wood, vacuum impregnation is used; Preferably, in the step S2 of preparing the transparent wood, curing is performed at room temperature and pressure; Preferably, in the step of preparing the S3 transparent conductive composite material, the conductive material is an ITO layer; Preferably, in the step of preparing the S3 transparent conductive composite material, the sputtering power of the magnetron sputtering is 120-200 W, the sputtering time is 800 s, and the sputtering pressure is 0.5-1.2 Pa; Preferably, in the step of preparing the S3 transparent conductive composite material, the atmosphere in the magnetron sputtering chamber is nitrogen.
[0018] In a second aspect, the present invention provides a conductive composite material prepared by the above method.
[0019] In a third aspect, the present invention provides an application of the above-mentioned conductive composite material in preparing a photoelectric substrate material.
[0020] The technical solution of the present invention achieves the following beneficial technical effects: Optimize resin filling and material properties: Select epoxy resin with a refractive index that matches the wood to effectively fill the pores after delignification, greatly improving the mechanical strength, thermal stability and light transmittance of the wood.
[0021] Finely control the delignification process: Through the gradient segmented delignification process, a gentle and efficient delignification process is achieved, and the integrity and elastic modulus of the cellulose skeleton are retained, ensuring the stability of the cellulose skeleton structure and the reliability of subsequent processing, thereby improving the conductivity and transparency of the transparent conductive material.
[0022] Application of magnetron sputtering technology: Magnetron sputtering technology is used to uniformly deposit the conductive layer, avoiding the agglomeration problem in traditional coating methods and significantly improving the conductive properties and optical transmittance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 : The charge and discharge curves and physical diagram of transparent conductive wood used in electrochromic electrodes in Example 1 of the present invention.
[0024] Figure 2 : Transmittance curve diagram of transparent conductive wood applied to electrochromic electrode in Example 1 of the present invention.
[0025] Figure 3 : Scanning electron microscope image of the original wood (NW) of Example 1 of the present invention.
[0026] Figure 4 : Scanning electron microscope image of transparent conductive wood (ITW) according to Example 1 of the present invention.
[0027] Figure 5 : Scanning electron microscope image of the transparent conductive wood conductive layer (ITW) of Example 1 of the present invention.
[0028] Figure 6 : Transmittance curves of delignified wood (DW), transparent wood (TW), and transparent conductive wood (ITW) in Example 1 of the present invention.
[0029] Figure 7 : Mechanical strength curves of original wood (NW), delignified wood (DW), transparent wood (TW), and transparent conductive wood (ITW) in Example 1 of the present invention.
[0030] Figure 8 : A graph showing the change in potential energy of the transparent conductive wood prepared in Example 1 over time after being connected to different currents (1A, 2A, 4A and 5A).
[0031] Note: The discharge curves, capacitance change graphs and scanning electron microscope images of the electrochromic electrode materials prepared in other embodiments are similar to those in Embodiment 1 and are therefore not shown again. DETAILED DESCRIPTION Example 1
[0032] In this embodiment, the method for preparing a photoelectric substrate material using transparent wood and magnetron sputtering technology includes the following steps: S1, delignification; S1.1, wood chips were placed in a solution of sodium chlorite with a concentration of 2.5wt% and a pH of 4 (the pH of the solution was adjusted with glacial acetic acid), and the temperature was maintained at 90°C under magnetic stirring at 300rpm. After reacting for 1h, the wood chips were taken out and washed with deionized water for 3 times; S1.2, place the washed wood chips in a solution with a sodium chlorite concentration of 2.5wt% and a pH of 4.6 (the pH of the solution is adjusted with glacial acetic acid), and keep the temperature at 90°C at a magnetic stirring speed of 200rpm. After reacting for 1 hour, take out the wood chips and wash them with deionized water three times; S1.3, the washed wood chips were placed in a solution with a sodium chlorite concentration of 2.5wt% and a pH of 5.5 (the pH of the solution was adjusted with glacial acetic acid), and the temperature was maintained at 90°C at a magnetic stirring speed of 50rpm. After reacting for 1h, the wood chips were taken out and washed with deionized water for 3 times; S1.4, then rinse the wood chips in deionized water and soak them in anhydrous ethanol for storage; S2. Preparation of transparent wood; The mass ratio of epoxy resin and curing agent was 3:1 to prepare the impregnation solution. After the solution was prepared, the delignified wood was placed at the bottom of a polytetrafluoroethylene culture dish and 5×10 -2 Pa vacuum environment for 2 hours, and the deflation-vacuuming process is repeated every 30 minutes. After the impregnation is completed, the wood chips are taken out of the impregnation liquid, placed in a normal temperature and pressure environment for 12 hours to solidify, and then taken out to make samples; S3. Preparation of transparent conductive composite materials; The sputtering power was 120W, the sputtering time was 800s, and the sputtering pressure was 1.2Pa. The atmosphere in the chamber was nitrogen. The target material was ITO target 99.99% (In2O3:SnO2=90:10 wt%) φ60*3mm bound to 2mm copper back target. The rotation speed of the sample stage during the reaction was 15rpm. After the reaction, the wood chips were washed and dried with anhydrous ethanol. The samples were marked as ITW. 120-1.2 .
[0033] The ITW prepared in this example 120-1.2 The square resistance is about 132Ω / sq, and WO3 magnetron sputtering is performed on its surface. After sputtering, the wood chips are washed and dried with anhydrous ethanol. The electrochemical performance of the electrode is tested with a three-electrode system in 1M LiClO4 as an electrolyte. In the potential window of -1.5V-1.5V, the switching time of the electrochromic electrode prepared by the present invention is about 6s, the light modulation amplitude at 660nm is 62%, and the quality coefficient can reach 27.8.
[0034] from Figure 1 It can be seen that: as the charging and discharging process proceeds, the electrode can show obvious color changes; Figure 2 It can be seen that after the electrochromic process occurs, the transmittance of the electrode changes significantly, and the transmittance change value at the light wavelength of 660nm is 34%, indicating that the material has a good light modulation effect; Figures 3 to 7It can be seen that In and Sn elements appear on the surface of the transparent conductive substrate prepared in this example, the film thickness is about 500nm, and the surface is relatively uniform and flat, indicating that a good quality conductive layer can be prepared by the magnetron sputtering method, and the thickness is low, which has little effect on the transmittance of transparent wood. The square resistance of the transparent conductive wood obtained in this example is about 132Ω / sq, the transmittance is 82% at 660nm, and the tensile strength reaches 160MPa. Example 2
[0035] In this embodiment, a method for preparing a photovoltaic substrate material using transparent wood and magnetron sputtering technology is used. The difference between this method and Embodiment 1 is that the sputtering pressure is 1.0 Pa, and the sample is marked as ITW. 120-1.0 ; Others are the same.
[0036] The ITW prepared in this example 120-1.0 The square resistance is about 113Ω / sq, and WO3 magnetron sputtering is performed on its surface. After sputtering, the wood chips are washed and dried with anhydrous ethanol. The electrochemical performance of the electrode is tested with a three-electrode system in 1M LiClO4 as an electrolyte. In the potential window of -1.5V-1.5V, the light modulation amplitude of the electrochromic electrode prepared in this example at 660nm is 65%, and the quality coefficient can reach 23.2. Example 3
[0037] In this embodiment, a method for preparing a photoelectric substrate material using transparent wood and magnetron sputtering technology is used. The difference between this method and Embodiment 1 is that the sputtering pressure is 1.4 Pa, and the sample is marked as ITW. 120-1.4 ; Others are the same.
[0038] The ITW prepared in this example 120-1.4 The square resistance is about 253Ω / sq, and WO3 magnetron sputtering is performed on its surface. After sputtering, the wood chips are washed and dried with anhydrous ethanol. The electrochemical performance of the electrode is tested with a three-electrode system in 1M LiClO4 as an electrolyte. In the potential window of -1.5V-1.5V, the light modulation amplitude of the electrochromic electrode prepared in this example at 660nm is 32%, and the quality coefficient can reach 9.7. Example 4
[0039] In this embodiment, a method for preparing a photoelectric substrate material using transparent wood and magnetron sputtering technology is used. The difference between this embodiment and embodiment 1 is that the sputtering power is 150W, and the sample is marked as ITW. 150-1.2 ; Others are the same.
[0040] The ITW prepared in this example 120-1.2The square resistance is about 133Ω / sq, and WO3 magnetron sputtering is performed on its surface. After sputtering, the wood chips are washed and dried with anhydrous ethanol. The electrochemical performance of the electrode is tested with a three-electrode system in 1M LiClO4 as an electrolyte. In the potential window of -1.5V-1.5V, the light modulation amplitude of the electrochromic electrode prepared in this example at 660nm is 45%, and the quality coefficient can reach 12.4.
[0041] The difference between Example 1, Example 2 and Example 3 is the different sputtering pressures. The sputtering pressure in Example 1 is 1.2 Pa, the sputtering pressure in Example 2 is 1 Pa, and the sputtering pressure in Example 3 is 1.4 Pa. The ITW prepared in Example 1 120-1.2 The square resistance is about 132Ω / sq, the light modulation amplitude of the prepared electrochromic electrode at 660nm is 62%, and the quality factor can reach 27.8. 120-1.0 The square resistance is about 113Ω / sq, the light modulation amplitude of the prepared electrochromic electrode at 660nm is 65%, and the quality factor can reach 23.2. 120-1.0 The square resistance is about 253Ω / sq, and the light modulation amplitude of the prepared electrochromic electrode at 660nm is 32%, and the quality factor can reach 9.7. It can be seen that the comprehensive performance of the product prepared when the sputtering pressure is 1.2Pa is better. When the sputtering pressure is lower, the light modulation amplitude of the product increases slightly, but the quality factor of the product decreases significantly. Excessive sputtering pressure will lead to a significant decrease in the light modulation amplitude and quality factor.
[0042] The difference between Example 1 and Example 4 lies in the different sputtering powers. The sputtering power in Example 1 is 120 W, and the sputtering power in Example 4 is 150 W. Compared with the product made in Example 1, the high light modulation amplitude and quality factor of the product made in Example 4 are greatly reduced.
[0043] Table 1 Product performance parameters of Examples 1-4
[0044] Comparative Example 1 A method for preparing a transparent conductive composite material comprises the following steps: S1, delignification; S1.1, wood chips were placed in a solution of sodium chlorite with a concentration of 2.5wt% and a pH of 4.6 (the pH of the solution was adjusted with glacial acetic acid), and the temperature was maintained at 90°C at a magnetic stirring speed of 300rpm. After reacting for 1h, the wood chips were taken out and washed with deionized water for 3 times; S1.2, the washed wood chips were placed in a fresh solution of sodium chlorite with a concentration of 2.5wt% and a pH of 4.6 (the pH of the solution was adjusted with glacial acetic acid), and the temperature was maintained at 90°C at a magnetic stirring speed of 200rpm. After reacting for 1h, the wood chips were taken out and washed with deionized water for 3 times; S1.3, then place the washed wood chips in a fresh solution with a sodium chlorite concentration of 2.5wt% and a pH of 4.6 (the pH value of the solution is adjusted with glacial acetic acid), and keep the temperature at 90°C at a magnetic stirring speed of 50rpm. After reacting for 1h, take out the wood chips and wash them with deionized water three times; S1.4, then rinse the wood chips in deionized water and soak them in anhydrous ethanol for storage; S2. Preparation of transparent wood The mass ratio of epoxy resin and curing agent was 3:1 to prepare the impregnation solution. After the solution was prepared, the delignified wood was placed at the bottom of a polytetrafluoroethylene culture dish and 5×10 -2 Immerse in a vacuum environment of Pa for 2 hours, and repeat the deflation-vacuuming process every 30 minutes; After the impregnation, the wood chips were taken out from the impregnation solution, placed in a normal temperature and pressure environment for 12 hours to solidify, and then removed to make samples; S3. Preparation of transparent conductive composite materials; The sputtering power was 120W, the sputtering time was 800s, and the sputtering pressure was 1.2Pa. The atmosphere in the chamber was nitrogen. The target material was ITO target 99.99% (In2O3:SnO2=90:10 wt%) φ60*3mm, bound with a 2mm copper back target. The rotation speed of the sample stage during the reaction was 15rpm. After the reaction, the wood chips were washed and dried with anhydrous ethanol. The samples were marked as ITW. 120-1.2(1) .
[0045] Comparative Example 2 A method for preparing a transparent conductive composite material comprises the following steps: S1, delignification; S1.1, wood chips were placed in a solution of sodium chlorite with a concentration of 2.5wt% and a pH of 4 (the pH of the solution was adjusted with glacial acetic acid), and the temperature was maintained at 90°C at a magnetic stirring speed of 300rpm. After reacting for 1h, the wood chips were taken out and washed with deionized water for 3 times; S1.2, place the washed wood chips in a solution with a sodium chlorite concentration of 2.5wt% and a pH of 4.6 (the pH of the solution is adjusted with glacial acetic acid), and keep the temperature at 90°C at a magnetic stirring speed of 300rpm. After reacting for 1h, take out the wood chips and wash them with deionized water three times; S1.3, the washed wood chips were placed in a solution with a sodium chlorite concentration of 2.5wt% and a pH of 5.5 (the pH of the solution was adjusted with glacial acetic acid), and the temperature was maintained at 90°C at a magnetic stirring speed of 300rpm. After reacting for 1h, the wood chips were taken out and washed with deionized water for 3 times; S1.4, then rinse the wood chips in deionized water and soak them in anhydrous ethanol for storage; S2. Preparation of transparent wood; The mass ratio of epoxy resin and curing agent was 3:1 to prepare the impregnation solution. After the solution was prepared, the delignified wood was placed at the bottom of a polytetrafluoroethylene culture dish and 5×10 -2 Pa vacuum environment immersion for 2h, and the deflation-vacuuming process was repeated every 30 minutes; After the impregnation, the wood chips were taken out from the impregnation solution, placed in a normal temperature and pressure environment for 12 hours to solidify, and then removed to make samples; S3. Preparation of transparent conductive composite materials; The sputtering power was 120W, the sputtering time was 800s, and the sputtering pressure was 1.2Pa. The atmosphere in the chamber was nitrogen. The target material was ITO target 99.99% (In2O3:SnO2=90:10 wt%) φ60*3mm bound to 2mm copper back target. The rotation speed of the sample stage during the reaction was 15rpm. After the reaction, the wood chips were washed and dried with anhydrous ethanol. The samples were marked as ITW. 120-1.2(2) .
[0046] Comparative Example 3 A method for preparing a transparent conductive composite material comprises the following steps: S1. Delignification S1.1, wood chips were placed in a solution of 5wt% sodium chlorite and pH 4 (the pH value of the solution was adjusted with glacial acetic acid), and the temperature was maintained at 90°C at a magnetic stirring speed of 300rpm. After reacting for 1h, the wood chips were taken out and washed with deionized water for 3 times; S1.2, place the washed wood chips in a solution with a sodium chlorite concentration of 5wt% and a pH of 4.6 (the pH of the solution is adjusted with glacial acetic acid), and keep the temperature at 90°C at a magnetic stirring speed of 200rpm. After reacting for 1h, take out the wood chips and wash them with deionized water for 3 times; S1.3, the washed wood chips were placed in a solution of 4wt% sodium chlorite and pH 5.5 (the pH value of the solution was adjusted with glacial acetic acid), and the temperature was maintained at 90°C at a magnetic stirring speed of 50 rpm. After reacting for 1 hour, the wood chips were taken out and washed with deionized water for 3 times; S1.4, then rinse the wood chips in deionized water and soak them in anhydrous ethanol for storage; S2. Preparation of transparent wood; The mass ratio of epoxy resin and curing agent was 3:1 to prepare the impregnation solution. After the solution was prepared, the delignified wood was placed at the bottom of a polytetrafluoroethylene culture dish and 5×10 -2 Immerse in a vacuum environment of Pa for 2 hours, and repeat the deflation-vacuuming process every 30 minutes; After the impregnation, the wood chips were taken out from the impregnation solution, placed in a normal temperature and pressure environment for 12 hours to solidify, and then removed to make samples; S3. Preparation of transparent conductive composite materials; The sputtering power was 120W, the sputtering time was 800s, and the sputtering pressure was 1.2Pa. The atmosphere in the chamber was nitrogen. The target material was ITO target 99.99% (In2O3:SnO2=90:10 wt%) φ60*3mm bound to 2mm copper back target. The rotation speed of the sample stage during the reaction was 15rpm. After the reaction, the wood chips were washed and dried with anhydrous ethanol. The samples were marked as ITW. 120-1.2(3) .
[0047] Comparative Example 4 A method for preparing a transparent conductive composite material comprises the following steps: S1, delignification; S1.1, wood chips were placed in a solution of 5wt% sodium chlorite and pH 4.6 (the pH value of the solution was adjusted with glacial acetic acid), and the temperature was maintained at 90°C at a magnetic stirring speed of 300rpm. After reacting for 1h, the wood chips were taken out and washed with deionized water for 3 times; S1.2, place the washed wood chips in a solution with a sodium chlorite concentration of 5wt% and a pH of 4.6 (the pH of the solution is adjusted with glacial acetic acid), and keep the temperature at 90°C at a magnetic stirring speed of 200rpm. After reacting for 1h, take out the wood chips and wash them with deionized water for 3 times; S1.3, then place the washed wood chips in a solution with a sodium chlorite concentration of 5wt% and a pH of 4.6 (the pH of the solution is adjusted with glacial acetic acid), and keep the temperature at 90°C at a magnetic stirring speed of 50rpm. After reacting for 1h, take out the wood chips and wash them with deionized water three times; S1.4, then rinse the wood chips in deionized water and soak them in anhydrous ethanol for storage; S2. Preparation of transparent wood; The mass ratio of epoxy resin and curing agent was 3:1 to prepare the impregnation solution. After the solution was prepared, the delignified wood was placed at the bottom of a polytetrafluoroethylene culture dish and 5×10 -2 Immerse in a vacuum environment of Pa for 2 hours, and repeat the deflation-vacuuming process every 30 minutes; After the impregnation, the wood chips were taken out from the impregnation solution, placed in a normal temperature and pressure environment for 12 hours to solidify, and then removed to make samples; S3. Preparation of transparent conductive composite materials; The sputtering power was 120W, the sputtering time was 800s, and the sputtering pressure was 1.2Pa. The atmosphere in the chamber was nitrogen. The target material was ITO target 99.99% (In2O3:SnO2=90:10 wt%) φ60*3mm bound to 2mm copper back target. The rotation speed of the sample stage during the reaction was 15rpm. After the reaction, the wood chips were washed and dried with anhydrous ethanol. The samples were marked as ITW. 120-1.2(4) .
[0048] Comparative Example 5 The difference from Example 1 is that after the impregnation, the wood chips are taken out from the impregnation liquid, placed in a normal pressure environment and heated to 60°C for 2 hours, and then taken out to make samples, and the samples are marked as ITW. 120-1.2(5) .
[0049] In Example 1, three staged impregnations are used to remove lignin, the concentration of sodium chlorite used in each stage is the same, the pH value of the impregnation solution used in each stage is different and gradually increases, and the stirring rate used in each stage is different and gradually decreases. The process parameters of delignification in Comparative Examples 1-4 are different from those in Example 1. The difference between Comparative Example 1 and Example 1 is that the pH value of the impregnation solution used in the three stages is the same; the difference between Comparative Example 2 and Example 1 is that the stirring rate used in the three stages is the same; the difference between Comparative Example 3 and Example 1 is that a large concentration of sodium chlorite is used; the difference between Comparative Example 4 and Example 1 is that a large concentration of sodium chlorite is used, and the pH value used in each stage is the same.
[0050] In Example 1, room temperature and pressure curing is adopted for 12 hours. The difference between Comparative Example 5 and Example 1 is that heat curing at 60° C. is adopted for curing for 2 hours.
[0051] The product performance parameters of Example 1 and Comparative Examples 1-5 are shown in Table 2. In Comparative Example 1, the three stages of delignification processes all use the same pH value (4.6), and the pH of the third stage reaction conditions is still relatively low. The third stage uses a highly reactive treatment solution, which continues to react violently with the cellulose skeleton, causing the pores in the cellulose skeleton to collapse, resulting in partial pore closure; and, the elastic modulus of the cellulose skeleton is too low, affecting its supporting role in the subsequent resin impregnation step. This structural change in the cellulose skeleton affects the uniform filling of the resin, resulting in the product having lower light transmittance and higher square resistance.
[0052] In comparative example 2, a constant stirring rate was maintained during the three-stage delignification process. This caused the wood structure to be continuously subjected to mechanical impact at a high rotation speed, which easily led to pore collapse and partial structural damage. The destruction of the pore structure significantly affected the permeability and filling uniformity of the resin, thereby reducing the transparency of the product and increasing the square resistance of the product.
[0053] Comparative Example 3 uses a higher sodium chlorite concentration (5 wt%), which results in a too fast reaction rate and excessive attack on the wood structure. High concentrations of chemical reagents improve the efficiency of delignification, but also increase the risk of attack on the cellulose skeleton, resulting in pore collapse and structural integrity damage, which seriously affects the effect of subsequent resin filling, reduces the transparency of the material, and significantly increases the square resistance.
[0054] Comparative Example 4 combines high sodium chlorite concentration (5 wt%) and constant pH value (4.6), and has the disadvantages of Comparative Examples 1 and 3. The high concentration of chemical reagents and the strong acidic environment work together to aggravate the destruction of the wood structure, resulting in more serious pore collapse and structural damage. In this case, the resin filling effect is extremely poor, the transparency of the wood is significantly reduced, and the square resistance is greatly increased.
[0055] Comparative Example 5 uses a heat curing process (60°C, 2 hours). During the process of returning to room temperature after curing, the transparent wood will shrink to a certain extent. This thermal expansion and contraction effect not only affects the dimensional stability of the transparent wood, but also changes its microstructure, resulting in a decrease in light transmittance. In addition, heat treatment may cause uneven release of stress inside the resin, making the surface of the transparent wood uneven, further affecting the quality of the conductive layer, and ultimately increasing the square resistance.
[0056] The present invention uses a lower sodium chlorite concentration, which can more gently remove lignin and prevent the cellulose skeleton from overreacting. Compared with the 5 wt% reaction concentration used in Comparative Examples 3 and 4, Example 1 uses a more moderate 2.5 wt% sodium chlorite concentration. The lower reaction concentration reduces the drastic impact on the wood structure and reduces the erosion of sodium perchlorite on cellulose and hemicellulose, thereby better maintaining the integrity and strength of the cellulose skeleton.
[0057] The present invention uses a gradual increase in pH value, from pH 4.0 to pH 5.5. Under strong acid conditions, although the delignification intensity is high, there is a risk of excessive erosion of cellulose, which may lead to damage to the structural integrity and degradation of mechanical properties. Adjusting the pH can more gently remove the remaining lignin, while effectively retaining the integrity and strength of cellulose, maintaining the stability of the wood structure and the necessary elastic modulus, and ensuring that the transparent wood can maintain structural stability during subsequent processing.
[0058] The present invention adopts a gradient-reduced stirring speed, and as the reaction progresses, the stirring speed is reduced from 300rpm to 50rpm. In the early stage of the delignification reaction, a higher stirring rate is feasible because the pore structure of the wood is relatively stable at this time and can withstand greater physical stress. However, as the delignification process advances, the pore structure inside the wood gradually becomes fragile and the elastic modulus decreases. If a high speed is continued to be maintained in the later stage of delignification, the risk of pore collapse will increase, thereby affecting the microstructure and final transparency of the wood, so it is necessary to reduce the stirring speed. This design is intended to reduce the impact of physical stress on the wood structure that has become more fragile, prevent pore collapse, thereby maintaining good permeability and mechanical support capacity, and is conducive to uniform penetration in the subsequent resin filling step.
[0059] The present invention adopts a room temperature curing process to avoid micro cracks caused by the difference in thermal shrinkage of different materials during the thermal curing process. By ensuring that the cellulose skeleton has an appropriate elastic modulus, the structural collapse caused by the fluidity of the impregnated resin before curing is effectively prevented, thereby ensuring the mechanical stability and surface flatness of the transparent wood surface.
[0060] The present invention achieves a more accurate and efficient delignification process by synergistically regulating multiple factors (such as sodium chlorite concentration, pH value, stirring rate, room temperature curing, etc.). This method not only reduces the reaction intensity of delignification, but also retains the structural integrity and mechanical properties of the wood to the maximum extent, providing an ideal base material for subsequent processing.
[0061] Table 2 Product performance parameters of Example 1 and Comparative Examples 1-5
[0062] The above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the claims of this patent application.
Claims
1. A method for preparing a conductive composite material, comprising the following steps: S1, delignification, placing wood chips in sodium chlorite solution to remove lignin; S2, preparation of transparent wood, impregnating the cellulose skeleton from which lignin has been removed with epoxy resin, and curing the resin to obtain transparent wood; S3. Preparation of transparent conductive composite materials: using magnetron sputtering technology to sputter conductive materials on the surface of transparent wood to obtain transparent conductive composite materials.
2. A method for preparing a conductive composite material according to claim 1, characterized in that: The delignification process in step S1 is a gradient segmented treatment, including three stages; the pH value gradient of the solution used in the three-stage delignification process increases, and the stirring speed gradient used in the three-stage delignification process decreases.
3. A method for preparing a conductive composite material according to claim 1, characterized in that: In step S1, the concentration of sodium chlorite remains unchanged at 2.5 wt %.
4. The method for preparing a conductive composite material according to claim 1 is characterized in that: In step S1, the pH values of the solutions used are 4, 4.6 and 5.5 respectively.
5. The method for preparing a conductive composite material according to claim 1, characterized in that: In step S1, the stirring speeds adopted are 300 rpm, 200 rpm and 50 rpm respectively.
6. The method for preparing a conductive composite material according to claim 1, characterized in that: In step S2, the curing process is selected to be curing at room temperature and pressure.
7. The method for preparing a conductive composite material according to claim 1, characterized in that: In step S3 of preparing the transparent conductive composite material, the conductive material is an ITO layer.
8. The method for preparing a conductive composite material according to claim 1, characterized in that: In the step S3 of preparing the transparent conductive composite material, the sputtering power of the magnetron sputtering is 120-200 W, the sputtering time is 800 s, and the sputtering pressure is 0.5-1.2 Pa.
9. A conductive composite material prepared by the method according to claims 1-8.
10. Use of the conductive composite material according to claim 9 in preparing a photoelectric substrate material.
Citation Information
Patent Citations
Preparation method of flexible cellulose-based transparent conductive material
CN106205876A
Preparation method of transparent and conductive flexible wood composite material
CN109049215A